Contribution of large genomic rearrangements in PALB2 to familial breast cancer: implications for genetic testing. Issue 2 (8th April 2022) - Li, Na; Zethoven, Magnus; McInerny, Simone; Healey, Eliza; DeSilva, Dilanka; Devereux, Lisa; Scott, Rodney J; James, Paul A; Campbell, Ian G
Abstract : Background: PALB2 is the most important contributor to familial breast cancer after BRCA1 and BRCA2 . Large genomic rearrangements (LGRs) in BRCA1 and BRCA2 are routinely assessed in clinical testing and are a significant contributor to the yield of actionable findings. In contrast, the contribution of LGRs in PALB2 has not been systematically studied. Methods: We performed targeted sequencing and real-time qPCR validation to identify LGRs in PALB2 in 5770 unrelated patients with familial breast cancer and 5741 cancer-free control women from the same Australian population. Results: Seven large deletions ranging in size from 0.96 kbp to 18.07 kbp involving PALB2 were identified in seven cases, while no LGRs were identified in any of the controls. Six LGRs were considered pathogenic as they included one or more exons of PALB2 and disrupted the WD40 domain at the C terminal end of the PALB2 protein while one LGR only involved a partial region of intron 10 and was considered a variant of unknown significance. Altogether, pathogenic LGRs identified in this study accounted for 10.3% (6 of 58) of the pathogenic PALB2 variants detected among the 5770 families with familial breast cancer. Conclusions: Our data show that a clinically important proportion of PALB2 pathogenic mutations in Australian patients with familial breast cancer are LGRs. Such observations have provided strong support for inclusion of PALB2 LGRs in routine clinical genetic testing.